2022
DOI: 10.1016/j.cub.2021.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Unique spatiotemporal fMRI dynamics in the awake mouse brain

Abstract: Highlights d fMRI networks in awake mice depart from underlying anatomical structure d fMRI dynamics in wakeful mice is critically shaped by arousal-related nuclei d Occurrence and topography of rsfMRI coactivation patterns define conscious states d fMRI coactivation dynamics defines a signature of consciousness in the mouse brain

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(146 citation statements)
references
References 73 publications
13
125
2
Order By: Relevance
“…In contrast, CBF decreases in rats given dexmedetomidine (Ganjoo et al, 1998). The frequency of spontaneous BOLD fluctuations is increased in the mice under a combination of isoflurane and medetomidine (Grandjean et al, 2017b) which is different from 1/f infraslow spectra usually observed with light isoflurane and halothane (Gutierrez-Barragan et al, 2019) or in awake mice (Gutierrez-Barragan et al, 2022) and humans (Fox et al, 2007). Specifically, for rs-fMRI, networks are more highly localized under light isoflurane anesthesia and become less spatially specific under deep isoflurane anesthesia (e.g., 1.8% isoflurane), and much of the specificity under deep isoflurane anesthesia was recovered after global signal regression .…”
Section: Anesthesiamentioning
confidence: 58%
See 3 more Smart Citations
“…In contrast, CBF decreases in rats given dexmedetomidine (Ganjoo et al, 1998). The frequency of spontaneous BOLD fluctuations is increased in the mice under a combination of isoflurane and medetomidine (Grandjean et al, 2017b) which is different from 1/f infraslow spectra usually observed with light isoflurane and halothane (Gutierrez-Barragan et al, 2019) or in awake mice (Gutierrez-Barragan et al, 2022) and humans (Fox et al, 2007). Specifically, for rs-fMRI, networks are more highly localized under light isoflurane anesthesia and become less spatially specific under deep isoflurane anesthesia (e.g., 1.8% isoflurane), and much of the specificity under deep isoflurane anesthesia was recovered after global signal regression .…”
Section: Anesthesiamentioning
confidence: 58%
“…In contrast, CBF decreases in rats given dexmedetomidine ( Ganjoo et al, 1998 ). The frequency of spontaneous BOLD fluctuations is increased in the mice under a combination of isoflurane and medetomidine ( Grandjean et al, 2017b ) which is different from 1/f infraslow spectra usually observed with light isoflurane and halothane ( Gutierrez-Barragan et al, 2019 ) or in awake mice ( Gutierrez-Barragan et al, 2022 ) and humans ( Fox et al, 2007 ).…”
Section: Acquisition Parameters Conditions and Confounds In Rodents C...mentioning
confidence: 72%
See 2 more Smart Citations
“…The use of brain templates is common for MRI recorded data ( Badea et al, 2019 ; Gutierrez-Barragan et al, 2022 ). However, for LSFM recorded data the same approach is complicated by the many different factors influencing tissue morphology and subsequent atlas registration ( Figures 1A–C ).…”
Section: Generating Digital Brain Mapsmentioning
confidence: 99%